PANCASILA SEBAGAI SUMBER DARI SEGALA SUMBER HUKUM - Fatimah Ratna Wijayanthi (The Juris, 2021)
In Indonesia, since time immemorial, they have known what is described for each perspective, cooperative social interaction and order and peace of life. Pancasila as a system of philosophy, ideology and basic lawof the state in the administration of the state law of the Republic of Indonesia, is placed on the list as the source of all sources of law, in the sense that all statutory regulations must contain and animate the values ??of Pancasila. In Politics Pancasila is the source of all sources law is a political agreement. Pancasila as the source of all sources of law within the boundaries of positive law, because it is rooted in the law of religious teachings which is rooted in revelation, as Pancasila is a failure of religion. In compiling the 1945 Constitution, the founders of the Indonesian state and nation agreed to establish Pancasila as the Philosophical Foundation of the State to be formed. Then the five points of Pancasila were included in the Preamble to the 1945 Constitution, which is an integral part of the body of the Constitution which was passed on August 18, 1945.